2016
DOI: 10.1080/02688697.2016.1208809
|View full text |Cite
|
Sign up to set email alerts
|

Connectome analysis for pre-operative brain mapping in neurosurgery

Abstract: Object: Brain mapping has entered a new era focusing on complex network connectivity. Central to this is the search for the connectome or the brains ‘wiring diagram’. Graph theory analysis of the connectome allows understanding of the importance of regions to network function, and the consequences of their impairment or excision. Our goal was to apply connectome analysis in patients with brain tumours to characterise overall network topology and individual patterns of connectivity alterations. Methods: Resting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 63 publications
2
47
0
Order By: Relevance
“…While a tumor is growing, penetrating, and taking places with more surrounding brain tissues, its influence on the brain connectomics could widely spread. The brain may evolve and adapt to the neoplasm, leading to other indirect, plastic changes at "normal appearing" regions or even on the unaffected side (Hart et al 2016a;Maesawa et al 2015;Ghumman et al 2016;Wang et al 2010). Hart et al (2016b) suggested that different tumor locations might affect different functional networks.…”
Section: Prognostic Values Of Brain Connectomics and Radiomicsmentioning
confidence: 99%
See 2 more Smart Citations
“…While a tumor is growing, penetrating, and taking places with more surrounding brain tissues, its influence on the brain connectomics could widely spread. The brain may evolve and adapt to the neoplasm, leading to other indirect, plastic changes at "normal appearing" regions or even on the unaffected side (Hart et al 2016a;Maesawa et al 2015;Ghumman et al 2016;Wang et al 2010). Hart et al (2016b) suggested that different tumor locations might affect different functional networks.…”
Section: Prognostic Values Of Brain Connectomics and Radiomicsmentioning
confidence: 99%
“…By calculating FCs for all pairs of the brain regions, a largescale whole-brain functional network (functional connectomics) can be constructed, and the network properties can be quantified using graph-theoretic analysis (Van Den Heuvel and Pol 2010;Rubinov and Sporns 2010;Bullmore and Sporns 2009;Wee et al, 2012). Brain functional connectomics features have been extensively used to reveal abnormalities caused by various neurological and psychiatric diseases (Rosazza and Minati 2011;Fox and Greicius 2010), including brain tumors (Hart et al 2016a(Hart et al , 2016bAerts et al 2016;van Dellen et al 2013;Xu et al 2013;Huang et al 2014). These studies have demonstrated that local lesion(s) could potentially have a much wider influence on the large-scale brain networks, causing network topographical changes and other system-level consequences (Wang et al 2009b;Wang et al 2010;Zhang et al 2009;Tijms et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because pathologies can cause difficulties in registration of normal brain atlases to the target image. Despite this, atlas based image segmentation like MAS is still widely used to segment pathological brain images [810]. …”
Section: Introductionmentioning
confidence: 99%
“…Despite advances in the new science of connectomics, techniques to directly study the function of white matter tracts in vivo have proved ambiguous. Cortical stimulation [7] and functional magnetic resonance imaging (fMRI) [12] are useful but constrained to identifying a focus of maximal activation. A purely anatomy-based approach such as tractography is challenging due to the definition of region of interest (ROI) and distortion of anatomical landmarks caused by lesions and brain plasticity [20].…”
Section: Introductionmentioning
confidence: 99%